EFFECT OF PHYTASE SUPPLEMENTATION IN LOW ENERGY-PROTEIN DIET ON THE PRODUCTION PERFORMANCE OF LAYER CHICKEN - Ponnuvel, P; Narayankutty, K; Jalaludeen, A; Anitha, P (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A production trial was carried out using 80 Single Comb White Leghorn hybrid Athulya layers to study the effect of phytase supplementation in low energy-protein diet on the production performance in comparison with standard layer ration for a period of 20 weeks. Phytase was supplemented at 0, 500 and 1000 units/kg in low energy- protein layer diet containing available phosphorus of 0.30 per cent from 21 to 40 weeks of age. Egg production, feed efficiency and egg weight were significantly improved (P<0.01) among phytase supplemented dietary treatments when compared with negative control. However, feed intake was not differed significantly.